Bioarqueologia: análisis preliminar del estado de conservación de una momia [Chisi Moix Muchik]en Cartavio, Provincia de Ascope 2024. - González Espino, David (2025)
Through bioarchaeology or molecular archaeology, it is possible to carry out actions based on human remains from the past. The objective of the work is to use strategies from bioarchaeology or molecular archaeology in the preliminary analysis of preventive conservation in a female mummy that is in an educational institution in the district of Cartavio, province of Ascope, region La Libertad. Regarding the research approach, it is quantitative, basic type and non-experimental design. Regarding the results, we have that 79.19% of the mummified body of the Moche girl is in good condition, at the level of injuries, 66.67% of the body presents a fact that can be produced by chemical or biological agents and the product of injuries in life, and regarding the storage space, it is inadequate with a percentage of 83.33%. Regarding the intervening variables, these are moderately related in a 0.528 fact that allows to verify the intervention. Finally, as for the conclusions we have that there is a natural mummification of the body of the Moche girl, apparently without the use of natural chemicals, however, in the space where it is currently stored it allows the acceleration of the deterioration of the body.